Comparative Analysis of Whole-Genome and Methylome Profiles of a Smooth and a Rough Mycobacterium abscessus Clinical Strain. Issue 1 (1st January 2020) - Chhotaray, Chiranjibi; Wang, Shuai; Tan, Yaoju; Ali, Amjad; Shehroz, Muhammad; Fang, Cuiting; Liu, Yang; Lu, Zhili; Cai, Xingshan; Hameed, H M Adnan; Islam, Md Mahmudul; Surineni, Goverdhan; et al.
Abstract: Mycobacterium abscessus is a fast growing Mycobacterium species mainly causing skin and respiratory infections in human. M. abscessus is resistant to numerous drugs, which is a major challenge for the treatment. In this study, we have sequenced the genomes of two clinical M. abscessus strains having rough and smooth morphology, using the single molecule real-time and Illumina HiSeq sequencing technology. In addition, we reported the first comparative methylome profiles of a rough and a smooth M. abscessus clinical strains. The number of N4-methylcytosine (4mC) and N6-methyladenine (6mA) modified bases obtained from smooth phenotype were two-fold and 1.6 fold respectively higher than that of rough phenotype. We have also identified 4 distinct novel motifs in two clinical strains and genes encoding antibiotic-modifying/targeting enzymes and genes associated with intracellular survivability having different methylation patterns. To our knowledge, this is the first report about genome-wide methylation profiles of M. abscessus strains and identification of a natural linear plasmid (15 kb) in this critical pathogen harboring methylated bases. The pan-genome analysis of 25 M. abscessus strains including two clinical strains revealed an open pan genome comprises of 7596 gene clusters. Likewise, structural variation analysis revealed that the genome of rough phenotype strain contains more insertions and deletions than the smooth phenotype and that of the reference strain. A total of 391 single nucleotide variations responsible for the non-synonymous mutations were detected in clinical strains compared to the reference genome. The comparative genomic analysis elucidates the genome plasticity in this emerging pathogen. Furthermore, the detection of genome-wide methylation profiles of M. abscessus clinical strains may provide insight into the significant role of DNA methylation in pathogenicity and drug resistance in this opportunistic pathogen.